Educating women about normal female genital appearance variation - Sharp, Gemma; Tiggemann, M. (Elsevier BV, 2016)
The study investigated the effectiveness of two online resources aimed at improving women's knowledge of the variation in normal female genital appearance and their attitudes towards their own genitals. The first consisted of a photographic array of normal female genitals and the second consisted of a video addressing digital airbrushing of women's genitals in media images. A sample of 136 female undergraduate students were randomly assigned to view the photographs, video, both the photographs and video, or neither. The video significantly increased women's perceptions of genital appearance diversity as well as awareness of digital airbrushing of genital images. Owing to relatively low levels of genital appearance concern, there was no effect of either resource on women's attitudes towards their own genitals; however, women who viewed the video indicated they would pass on their knowledge to help other women. Our results suggest that an educational video could be a useful tool.